2019
DOI: 10.1080/19420889.2019.1568818
|View full text |Cite
|
Sign up to set email alerts
|

The jamming avoidance response in echolocating bats

Abstract: Bats face many sources of acoustic interference in their natural environments, including other bats and potential prey items that affect their ability to interpret the returning echoes of their biosonar signals. To be able to navigate and forage successfully, bats must be able to counteract this interference and one of the ways they achieve this is by altering the various parameters of their echolocation. We describe these changes in signal design within the context of a modified definition of the jamming avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Why then do bats exhibit JAR-like behaviors? Several previous studies reported that bats change their emission frequencies in response to nearby conspecifics ( Takahashi et al, 2014 ; Ibáñez et al, 2004 ; Chiu et al, 2009 ; Ulanovsky et al, 2004 ) or to the playback of masking signals ( Jones and Conner, 2019 ; Gillam et al, 2007 ; Gillam and Montero, 2016 ; Bates et al, 2008 ; Luo and Moss, 2017 ). Researchers have interpreted this behavior as a spectral jamming avoidance response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Why then do bats exhibit JAR-like behaviors? Several previous studies reported that bats change their emission frequencies in response to nearby conspecifics ( Takahashi et al, 2014 ; Ibáñez et al, 2004 ; Chiu et al, 2009 ; Ulanovsky et al, 2004 ) or to the playback of masking signals ( Jones and Conner, 2019 ; Gillam et al, 2007 ; Gillam and Montero, 2016 ; Bates et al, 2008 ; Luo and Moss, 2017 ). Researchers have interpreted this behavior as a spectral jamming avoidance response.…”
Section: Discussionmentioning
confidence: 99%
“…The question of how bats deal with conspecific masking ( Beleyur and Goerlitz, 2019 ; Jones and Conner, 2019 ) and whether they perform a spectral Jamming Avoidance Response (JAR) has been widely studied but is still under dispute. Many studies have suggested that bats change their echolocation frequencies when hunting at the presence of other bats ( Takahashi et al, 2014 ; Ibáñez et al, 2004 ; Chiu et al, 2009 ; Ulanovsky et al, 2004 ) or when exposed to playback of partially or fully overlapping signals ( Gillam et al, 2007 ; Gillam and Montero, 2016 ; Bates et al, 2008 ; Luo and Moss, 2017 ; Corcoran and Conner, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Note that this study was conducted in a fruit-eating bat. Most previous research has focused on insect-eating bats (Corcoran and Moss, 2017;Jones and Conner, 2019). One should consider the possibility that not all bats respond in the same way to acoustic interference.…”
Section: Bats Show Different Combinations Of Adaptations When Echolocating In the Presence Of An Acoustic Interferermentioning
confidence: 99%
“…Call-echo assignments become challenging, however, when biosonar signals from conspecifics overlap (Corcoran and Moss, 2017;Levin et al, 2013;Parsons et al, 2003;Ulanovsky and Moss, 2008). Under these circumstances, bats show a large repertoire of echolocation adjustments that are thought to improve signal extraction (for review, see Jones and Conner, 2019). These adjustments include shifting call spectra to reduce signal overlap, increasing call level to improve the signal-to-noise ratio, adapting call duration to reduce temporal overlap between signal and noise, and increasing the redundancy of echo information by emitting groups of calls (call strobes; Roverud and Grinnell, 1985a,b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation